ANALISIS STRUKTUR NARATIF PADA FILM MERRY RIANA MIMPI SEJUTA DOLAR DALAM MEMBANGUN ADEGAN DRAMATIK - Haryanto, Dwi (Institut Seni Budaya Indonesia Bandung, 2018)
The present study delved into the narrative structure of Merry Riana’s movie mimpi Sejuta Dolar in emerging dramatic scenes. The reserch objective was to probe the narrative structure in emerging dramatic scenes, based on four dramatic element proposed Elizabeth Lutters, evident in Merry Riana’s movie mimpi Sejuta Dolar. The research method operative was qualitative descriptive in nature, wich was deployed to scrutinized the problems under investigation, in-depth. The data analysis on the research object applied narrative analysis, wich dealt with actualizing dramatization. The theory cushioning the study was The Classical Hollywood Cinema created by David Bordwell, Janet Staiger, and Kristin Thompson, and four dramatic element proposed by Ellizabeth Lutters. The result of data analysis concluded that the dramatic element ebedded in the movie were conflict, suspense, curiosity and surprise. Four of those dramatic eleent were operative in tandem with the narrative element involving spece and time ad well as the objective of main character in making his dreams come true. The analysis employing the Classical Hollywood Cinema or narrative element proposed by David Bordwell, Janet Straiger, and Kristin Thompson resulted in a more complete elabroration of the dramatic scene.